2018
DOI: 10.3892/mmr.2018.9187
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑326 inhibits endometrial fibrosis by regulating TGF‑β1/Smad3 pathway in intrauterine adhesions

Abstract: Intrauterine adhesion (IUA), characterized by endometrial fibrosis, may lead to infertility and recurrent pregnancy loss. At present, there is no ideal therapy for IUA. Recent findings have revealed that microRNAs (miRNAs) have a decisive role in the regulation of fibrosis. The aim of the present study was to investigate the molecular mechanism of miRNAs in endometrial fibrosis. The present study compared the expression profiles of miRNAs between endometrial tissues from patients with IUA and normal endometria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 38 publications
2
41
0
Order By: Relevance
“…Under normal physiological conditions, TGF-β1 can promote the repair and healing of the injured site, making the extracellular matrix in a state of balance, while under pathological conditions, TGF-β1 can stimulate the expression of fibronectin and collagen, inhibit the degradation of the extracellular matrix, and lead to fibrosis and scar tissue formation [33]. Plenty of studies have confirmed that TGF-β1/Smad pathway dysregulation was an important mechanism in tissue fibrosis [34][35][36]. Smad2 and Smad3 are the major downstream regulators and promote TGF-β1 mediate the expression of key tissue fibrosis genes, while Smad7 serves as a negative feedback regulator of the pathway, thereby preventing TGF-β1-mediated fibrosis [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Under normal physiological conditions, TGF-β1 can promote the repair and healing of the injured site, making the extracellular matrix in a state of balance, while under pathological conditions, TGF-β1 can stimulate the expression of fibronectin and collagen, inhibit the degradation of the extracellular matrix, and lead to fibrosis and scar tissue formation [33]. Plenty of studies have confirmed that TGF-β1/Smad pathway dysregulation was an important mechanism in tissue fibrosis [34][35][36]. Smad2 and Smad3 are the major downstream regulators and promote TGF-β1 mediate the expression of key tissue fibrosis genes, while Smad7 serves as a negative feedback regulator of the pathway, thereby preventing TGF-β1-mediated fibrosis [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 has a specific role in the occurrence and progression of IUAs, and the expression levels of TGF-β1 and Smad3 are positively correlated with the severity of IUAs (15,45). Studies have revealed that miRNA-29b and miRNA-326 may improve endometrial fibrosis in primary human endometrial stromal cells, and can significantly decrease COL1A1, α-SMA and FN expression by inhibiting the TGF-β1/Smad signalling pathway (14,46). In order to investigate the potential mechanism underlying the anti-fibrosis effect of aspirin, the present study examined the expression levels of TGF-β1, Smad2 and Smad3 in the endometrial tissues of two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Following activation of TGF-β1, activated TGF-β1 binds to its receptor and activates downstream Smad signalling, including Smad2 and Smad3, which serves a crucial role in tissue fibrosis (6,7), including cardiac (8), liver (9), pulmonary (10), pancreatic (11) and renal fibrosis (12), and chronic autoimmune disease Sjögren's syndrome (SS) (13). The mechanism of the TGF-β1/Smad signalling pathway involved in the occurrence of intrauterine adhesions has been described previously (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found that IUA rat fibroblasts were arrested at G1 after treatment with mitomycin C. Moreover, mitomycin C promoted IUA rat fibroblast apoptosis. Mitomycin C inhibited IUA rat uterine fibroblasts to secrete collagen type I, a fibrotic marker that provides mechanical stability for tissues and serves as a functional environment for cells [29,30]. Endometrial fibrosis is associated with the development of IUA.…”
Section: Discussionmentioning
confidence: 99%